PENINGKATKAN MUTU HASIL BELAJAR IPS MENGGUNAKAN PENGELOLAAN KELAS DENGAN METODE PETA KONSEP - Bera, Lukas (Edum Journal, 2019)
The research sets purpose to increase the dtudi result of ips by using the draft map method for subject kind of job toward students at third grade in SDN XXV Wailiti in 2017 / 2018 . This research is actually a class measure research which has the students of third grade as its subject of research, consists of 9 schooolboys and 16 schoolgirls. It is done within 2 cycles and each cyele goes through planning, implementation, observation and reflection. While to assemble the data, it uses test, observation, documentation. The result of the research shows increases in teachers and students activity, and also the study result of students in IPS by using draf map method. The observation on the teachers activity on the firdt cycle at first meeting reaches 75% categorizet as good, and at the second neeting reaches 88,33% categorizet as good. The second cyle for the first meeting gets 90% for good category, and on the second it achieves 96,6% for very good category. While the students activity on the first cycle for the first meeting reaches 75% categorizet as good, and the second meeting reaches 83,33% categorizet as very good. On the second cycle at first meeting attains 87,5% for good category, second meeting achieves 95,83% categorizet as very good. Based on the study result of first cycle, students reach the average level become 66,6%. While the second cycle shows student in average level raises up to 81,6%. In summary, by using draft map method for subject kind of job can increase teachers skills, students activity and study result toward student at third grade in SDN XXV Wailiti, sub-ditrict of Alok Barat, Sikka Regency.